New York City Court Employment Project Evaluation Study, 1976-1979 ([Verlag nicht ermittelbar], 1984)
This study served as a controlled research evaluation of the New York City Court Employment Project (CEP) as it stood in 1976-1979. At the time of the study, CEP was an independent corporation under contract to New York City's Human Resources Administration. The ultimate aim of CEP was to change the income-generating behavior of its participants to reduce their subsequent criminal activity. CEP did this by diverting accused offenders from routine court procedures (criminal prosecution, sentencing, and possible incarceration) and instead placing them into jobs, training, or vocationally-oriented counseling services. Eligible defendants agreed to attend mandatory counseling sessions, to devise and execute individual plans for securing training and employment, and to avoid arrest and conviction during their participation. Charges were dismissed by the court if, at the end of six months, CEP counselors determined that the defendant had participated successfully. Research goals for this study were to accumulate data in order to: (1) assess the impact of diversion on recidivism and personal stability, (2) ascertain the outcome of court cases without diversion, and (3) assess the relationship of these outcomes to the social services aspect of diversion programs. The study compared a control group of non-CEP offenders with an experimental group of CEP participants to assess the program's effectiveness in helping offenders find and maintain employment or training and avoid criminal activity. Data were collected on 666 subjects, 410 in the experimental group and 256 in the control group. Three interviews were conducted at six-month intervals with each subject, initially to record self-reports about education, training, employment history, reliance on public assistance, criminal history, illegal activities, lifestyle, and utilization of social services, and then to maintain current information about their school, employment, income, and court processing status. In addition to the three personal interviews, official records data were obtained from a variety of agencies to gather information including criminal history, disposition of the case on which the defendant entered the research, information related to subsequent arrests, and (for members of the experimental group) information about participation in CEP. Other variables include attendance at counseling sessions, type of employment found, job attendance, self-evaluation of important life events and life satisfaction, social services programs utilized, and drug and alcohol use, as well as defendant's and defendant's parents' age, sex, and race.